Pengaruh Penerapan Problem Based Learning (Pbl) Berbantuan Media Pembelajaran Berbasis Video Terhadap Critical Thinking Siswa Kelas XI Manajemen Perkantoran SMK Negeri 2 Kediri - Prameswari Ade Yuhono, Lativa; Farida Panduwinata, Lifa (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE EFFECT OF THE IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) ASSISTED BY VIDEO-BASED LEARNING MEDIA ON THE CRITICAL THINKING OF STUDENTS OF CLASS XI OFFICE MANAGEMENT AT STATE VOCATIONAL HIGH SCHOOL 2 KEDIRIThis study aims to assess the critical thinking skills of class XI Office Management students at SMK Negeri 2 Kediri through the implementation of the Problem-Based Learning (PBL) mode lassisted by video media. The research uses a Quasi-Experimental Design method, specifically the Nonequivalent Control Group Design. The sample consists of 35 students from class XI MPK 2 and 34 students from class XI MPK 1. Data was collected from pretest and posttest results. Data analysis techniques included normality test, homogeneity test, Wilcoxon hypothesis test, and N-Gain test. The results of the hypothesis test show an Asymp. Sig. (2-tailed) value of 0.000, which is less than 0.05. Based on this result, it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, indicating that the application of the PBL model assisted by video-based learning media has a positive effect on the critical thinking abilities of class XI Office Management students at SMK Negeri 2 Kediri.